Analysis of ligament behaviour for healthyhuman leg with or without kneepad after kicking the ball - Muhamad Shafiq, Shahruddin (2013)
Ligament is tough bands of fibrous tissues that connect between two bones. Those bones are the tibia and femur bones. The knee structure is including the femur (thighbone), tibia (shinbone), ligament, meniscus, articular cartilage, tendon and patella (kneecap). The anterior cruciate ligament (ACL) connects the femur to the tibia at the center of the knee. It limits rotation and the forward motion of the tibia. The ACL injury was found to be the highest among others ligament. Running and kicking is the activities that frequently can cause the ACL injury. In this study, a three-dimensional finite element model of the human ACL was developed and the simulation of passive knee flexion was performed. The objective for this study is to investigate the behaviour of the ACL effect when using knee pad during the kicking activities in soccer game. The numerical modeling of passive knee flexion was performed, with and without applying the stress on the ACL. The analysis will consist of analysis with the kneepad and analysis the knee without the knee pad. Both of the analysis involved in knee posturer angles. The angles are 0⁰, 45⁰, 90⁰ and 155⁰ of knee flexion. The results show that 90⁰ flexion give highest stress value among other knee flexion. One possible explanation is that, the ligaments already reach its final stages for twisting. After this stage, the ligament will not twisting but it will start to bend. The ligament will bend until it reaches it bending limit.